Incorporation of copper into chitosan scaffolds promotes bone regeneration in rat calvarial defects. Issue 5 (17th September 2014) - D'Mello, Sheetal; Elangovan, Satheesh; Hong, Liu; Ross, Ryan D.; Sumner, D. Rick; Salem, Aliasger K.
Abstract The objective of this study was to investigate the effects of a copper loaded chitosan scaffold on bone regeneration in critical‐sized calvarial defects in rats. Chitosan scaffolds and copper‐chitosan scaffolds were fabricated and characterized by scanning electron microscopy (SEM). Chitosan and copper‐chitosan scaffolds were implanted into 5 mm diameter critical‐sized calvarial defects in Fisher 344 male rats. Empty defects (no scaffolds) were included as a control. After 4 weeks, the rats were sacrificed for microcomputed tomography (micro‐CT) and histological analysis of new bone tissue development. Microscopy images revealed the uniformly porous structure of chitosan and copper‐chitosan scaffolds. Significant bone regeneration was noted in the defects treated with copper‐chitosan scaffolds when evaluated using micro‐CT and histological analysis, when compared with other groups tested. On analysis of the micro‐CT scans, an eleven‐fold and a two‐fold increase in the new bone volume/total volume (BV/TV) % was found in defects treated with the copper‐chitosan scaffolds, when compared to empty defects and chitosan scaffolds, respectively. This study demonstrated the suitability of copper‐crosslinked chitosan scaffolds for bone tissue engineering and provides the first evidence that inclusion of copper ions in scaffolds can enhance tissue regeneration. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1044–1049, 2015.